Efficacy of inosine pranobex in frequently ill children with chronic Epstein-Barr virus infection: randomized study - E.N. Simovanyan; V.B. Denisenko; A.V. Grigoryan ("Paediatrician" Publishers LLC, 2011)
High incidence of acute respiratory infections (ARI) in immunocompromised frequently ill children with chronic Epstein-Barr infection forces the prescription of drugs with complex antivirus and immunocorrecting effect. The objective: to study the efficacy of inosine pranobex (Isoprinosine) in treatment of active Epstein-Barr virus infection in frequently ill children. Methods: patients were randomized in group of standard treatment (n = 24) and standard treatment + inosine pranobex 50 mg/kg of body weight divided to 3-4 parts daily (3 courses of 10 days every other 10 days). Primary efficacy criterion was the incidence of ARI episodes during 12 months of observation. Results: the treatment with inosine pranobex resulted in decrease of incidence (4 and 25%) and duration of ARI (5.6 ± 1.2 and 8.8 ± 3.3 days) compared to standard treatment. Besides, inosine pranobex decreased the frequency of lymphoproliferation, arthralgic and cardiac syndromes, favored to rapid elimination of serologic markers of Epstein-Barr virus replication and normalization of blood concentrations of interferon _ and interleukine 4. Side effects of treatment with inosine pranobex were not registered. Conclusion: inosine pranobex is efficient and safe drug in treatment of active form of chronic Epstein-Barr virus infection in frequently ill children. Key words: frequently ill children, Epstein-Barr virus, inosine pranobex, treatment.